Analisis Strategi Pengembangan Kompetensi Pegawai Pada Badan Kepegawaian Dan Pegembangan Sumber Daya Manusia Kabupaten Nias Utara - Agus Ratna Mawarni Harefa; Syah Abadi Mendrofa; Yamolala Zega; Sukaaro Waruwu (LPPM Universitas HKBP Nommensen, 2024)
Developing employee competency is crucial in improving the quality of public services. In the era of globalization and increasingly fierce competition, local governments are required to have superior human resources and be able to adapt quickly to change. Therefore, employee competency development strategies are very important to ensure the achievement of organizational goals in providing excellent service to the community. The variables in this research consist of 1 (one) single variable, namely: A single variable is a variable that only has one dimension or category. This variable only has one value or attribute for each unit of analysis. According to Sugiyono (2017: 39), research variables are